MEDIATION OF ORGANIZATIONAL COMMITMENT: EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF PUBLIC SERVICE EMPLOYEES - Ega Putri Puspa Sari (IAIN Surakarta, 2022)
Organizational citizenship behavior by mediating organizational commitment. The sample used is non- probability sampling with purposive sampling as many as 100 respondents of civil servants throughout Boyolali Regency. This study uses quantitative research methods using questionnaires as data collection materials which were analyzed with the help of IBM SPSS Software Version 23. The results of this study prove that perceived organizational support has a positive and significant effect on organizational citizenship behavior, organizational commitment. positive and significant effect on organizational citizenship behavior, and organizational commitment mediates the relationship between perceived organizational support and organizational citizenship behavior.